Tembusu Virus in Human, China. Issue 3 (1st April 2013) - Tang, Y.; Gao, X.; Diao, Y.; Feng, Q.; Chen, H.; Liu, X.; Ge, P.; Yu, C.
<x xml:space="preserve">Abstract</x> Summary Tembusu virus (TMUV) infection in ducks, geese and house sparrows was reported in China. To confirm the emergence of TMUV in humans, we investigated TMUV as a possible infection in duck industry workers in Shandong, China. Of 132 serum samples tested, 95 (71.9%) had TMUV antibodies. In oral swabs detection, 63 (47.7%) samples were positive for TMUV RNA. Nucleotide sequences of 277 bp coding the partial NS3 protein showed more than 99.5% identity with other duck TMUV strains, which can cause severe egg drop in ducks. These findings contribute to the realization that TMUV may be overlooked as a zoonotic transmission in China.